2002
DOI: 10.1074/jbc.m206851200
|View full text |Cite
|
Sign up to set email alerts
|

Two Nonadjacent Regions in Enteroaggregative Escherichia coli Flagellin Are Required for Activation of Toll-like Receptor 5

Abstract: Most Gram-negative bacteria express flagella, surface structures that confer motility. Flagella are composed of a basal body that serves as a rotatory motor, a filament that extends into the space around the bacterium to provide motive force, and a hook that connects the two. The filament consists of a long homopolymer of a single protein, flagellin, with a small cap protein at the end. Polymerization of flagellin occurs as a result of relatively conserved structures at the N and C termini, although the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 24 publications
(35 reference statements)
7
94
0
Order By: Relevance
“…Although the TLR5 dependence of Gram-negative flagellin signaling has been well documented, the structural requirements for the interaction between flagellin and TLR5 are only partially understood. Structure/function studies with soluble flagellin indicate that the amino and carboxyl constant regions are most critical for TLR5 signaling (22,23). We have shown that flagellin is active at concentrations in the picomolar to nanomolar range (24), a finding that is consistent with a very high affinity interaction.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Although the TLR5 dependence of Gram-negative flagellin signaling has been well documented, the structural requirements for the interaction between flagellin and TLR5 are only partially understood. Structure/function studies with soluble flagellin indicate that the amino and carboxyl constant regions are most critical for TLR5 signaling (22,23). We have shown that flagellin is active at concentrations in the picomolar to nanomolar range (24), a finding that is consistent with a very high affinity interaction.…”
supporting
confidence: 68%
“…The results of two recent studies (22,23) indicate that the conserved amino and carboxyl regions of flagellin are required for biologic activity. This appears to be in conflict with our observation (24) that a peptide containing only these two regions was inactive.…”
Section: Discussionmentioning
confidence: 99%
“…6). 110 Further exploration of the correlates of the primary sequence of flagellin and TLR5 agonism have now defined two regions: a 14-residue N-motif peptide (AA 95-108) and a 9-residue C-motif peptide (AA 441-449), deletions or mutagenesis of which result in abrogation of TLR5 signaling. 111 Flagellin has been demonstrated to induce maturation and chemokine production in human dendritic cells, 112 resulting in stimulation of T H 1 responses via IL-12p70 production, which depends on the phosphorylation of p38 and c-Jun N-terminal kinase 1/2 (JNK).…”
Section: Tlr5 Agonistic Flagellinmentioning
confidence: 99%
“…109 Random and site-directed mutagenesis of flagellin from enteroaggregative E. coli identified two regions in the conserved D1 domain that are required for interleukin-8 release and TLR5 activation in Caco-2 cells. 110 The transposon linker insertions which eliminate inflammatory activity (2H3, E8, F11, C5) are located near the midpoint of the α-helix formed by the C-terminal conserved domain of the protein (Fig. 6).…”
Section: Tlr5 Agonistic Flagellinmentioning
confidence: 99%
“…8 Flagellin contains two highly conserved N/C domains (D0 and D1) and one central hypervariable domain (D2/D3). [9][10][11] The hypervariable domain is vastly diverse in size and amino-acid composition among bacterial strains and species. 4 The conserved D0 and D1 domains are required for the immune activity of flagellin as a pathogen-associated molecular pattern.…”
Section: Introductionmentioning
confidence: 99%